2010
DOI: 10.4012/dmj.2009-075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different food colorants and polishing techniques on color stability of provisional prosthetic materials

Abstract: The main objective was to investigate the effects of different polishing techniques on the color stability of provisional prosthetic materials upon exposure to different staining agents by mimicking the oral environment in vitro. Fifty-six cylindrical specimens were prepared for each type of material: bis-acryl and light-polymerized composite resins, and methyl methacrylate-and ethyl methacrylatebased resins. The specimens were polished using seven different polishing techniques and then immersed in four diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
180
2
24

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(222 citation statements)
references
References 60 publications
(61 reference statements)
16
180
2
24
Order By: Relevance
“…These results corroborate the findings of previous studies that evaluated the color stability of different materials and observed that Protemp resin also presented high color change values 2,16 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results corroborate the findings of previous studies that evaluated the color stability of different materials and observed that Protemp resin also presented high color change values 2,16 .…”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been found in previous studies that also observed greater susceptibility to color change of bis-acrylic resins when in contact with pigmenting solutions 2,7 . Moreover, studies conducted by Haselton et al 4 and Turgut et al 17 pointed out the capacity of absorption and adsorption of pigmenting solutions to influence the color stability of acrylic resins.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations